Page 11 - Bahan Ajar Berbasis Flipped Learning pada materi Diferensial
P. 11

Penyelesaian

                                         3
                                               2
                         a.    (  ) = −   − 7  
                                                   ′
                                                                      2
                                             3
                              Misal:     = −   →    = −3   3−1  = −3  
                                            2
                                                                      1
                                                   ′
                                        = 7    →    = 7.2.    2−1  = 14   = 14  
                                                                                  2
                                                                     ′
                                                            ′
                                                                          ′
                              Jadi, jika   (  ) =    −    maka    (  ) =    −    = −3   − 14  

                         b.    (  ) = 4   + 15  
                                        2
                                                   ′
                                            2
                              Misal:     = 4    →    = 4.2.    2−1  = 8  
                                        = 15    →    = 15.    1−1  = 15.    = 15
                                                                       0
                                                   ′
                                                                         ′
                                                            ′
                              Jadi, jika  (  ) =    +    maka    (  ) =    +    = 8   + 15
                                                                    ′

                                        3
                         c.    (  ) = 9   − 3   +  5
                                                     2
                                                  ′
                                                                      2
                                            3
                              Misal:     = 9   →    = 9.3.    3−1  = 27  
                                                  ′
                                      ′
                                        = 3    →    = 3.    1−1  = 3
                                                           ′
                                       ′
                                        =  5  = 5   −2   →    = 5. (−2).    −2−1  = −10   −3  =  −10
                                              2                                               −3
                                                                          ′
                                                                                    ′
                                                                               ′
                              Jadi, jika   (  ) =    −    +    maka    (  ) =    −    +   
                                                                 ′
                                                                                     10
                                                                 ′
                                                                            2
                                                                   (  ) = 27   − 3 −
                                                                                       −3

                                          3
                         d.    (  ) = 5   − √   + 1
                                             2
                                                                  0
                                                 ′
                              Misal:     = 5   →    = 5.    1−1  = 5   = 5
                                                             2
                                                  2       2  −1    2 − 1   2
                                          3
                                        = √   =    3 →    =    3  =    3 =  3
                                                       ′
                                            2
                                                          3        3      3 √  
                                        = 1 →    = 0
                                                 ′
                                                                               ′
                              Jadi, jika   (  ) =    −    +    maka    (  ) =    −    +   ′
                                                                          ′
                                                                 ′
                                                                 ′
                                                                   (  ) = 5 −  3 2
                                                                            3 √  



               10 | T u r u n a n                                                      K e l a s   X I   S M A
   6   7   8   9   10   11   12   13   14   15   16